Essentials of materials science and engineering - Askeland, Donald R.; Wright, Wendelin J. (Boston, MA Cengage Learning, 2019)
This text provides students with a solid understanding of the relationship between structure, processing and properties of materials. It covers fundamentals in an integrated approach that emphasizes applications of new technologies enabled by engineered materials. Help your students understand the science of materials in order to select and deploy materials as responsible engineers with Askeland/Wright's Essentials of materials science and engineering, 4th edition. Your students develop a foundational understanding of why materials behave the way they do, and how they are best used in actual engineering practice. Students learn why materials display certain properties as they study how the structure and processing of materials results in these properties. The authors link fundamental concepts to practical applications, emphasizing the necessary basics without overwhelming readers with too much underlying chemistry or physics. This presentation is ideal for an introductory science of materials class taught at the sophomore or junior level and assumes knowledge of first-year courses in college-level chemistry and physics.
Introduction to materials science and engineering -- Atomic structure -- Atomic and ionic arrangements -- Imperfections in the atomic and ionic arrangements -- Atom and ion movements in materials -- Mechanical properties -- Strain hardening and annealing -- Principles of solidification -- Solid solutions and phase equilibrium -- Dispersion strengthening and eutectic phase diagrams -- Dispersion strengthening by phase transformations and heat treatment -- Heat treatment of steels and cast irons -- Nonferrous alloys -- Ceramics -- Polymers -- Composites: teamwork and synergy in materials -- Corrosion and wear.
Includes index.
Keywords: Materials; Materials science; Materials science -- Problems, exercises, etc